2022
DOI: 10.1007/s10899-022-10151-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gambling Disorder, Stressful Life Events, Gambling-Related Cognitive Distortions, Difficulty in Emotion Regulation, and Self-Control

Abstract: Gambling Disorder (GD) is a prominent psychiatric disorder affecting individuals worldwide. Research suggests that key risk factors for GD include stressful life events (SLEs) and specific psychological factors, such as gambling-related cognitive distortions. The present study investigated the potential mediating role of specific psychological factors (i.e., gambling-related cognitive distortions, difficulty in emotion regulation, and self-control) in the relationship between SLEs and GD. A cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Chronic sources of stress have also been linked to problem gambling, including homelessness (Vandenberg et al, 2022) trauma (Moore & Grubbs, 2021), the experience of mental health problems (Ronzitti et al, 2018) and stressful life events (Russell et al, 2022). Individuals who experience difficulty in managing affective states also tend to experience more severe problem gambling (Buen & Flack, 2022;Thurm et al, 2023). This is consistent with research that has found associations between the experience of anxiety and depression and problem gambling (Mide et al, 2023;Sundqvist & Wennberg, 2022;Vaughan & Flack, 2022).…”
supporting
confidence: 70%
“…Chronic sources of stress have also been linked to problem gambling, including homelessness (Vandenberg et al, 2022) trauma (Moore & Grubbs, 2021), the experience of mental health problems (Ronzitti et al, 2018) and stressful life events (Russell et al, 2022). Individuals who experience difficulty in managing affective states also tend to experience more severe problem gambling (Buen & Flack, 2022;Thurm et al, 2023). This is consistent with research that has found associations between the experience of anxiety and depression and problem gambling (Mide et al, 2023;Sundqvist & Wennberg, 2022;Vaughan & Flack, 2022).…”
supporting
confidence: 70%
“…A higher level of intolerance of uncertainty is likely to drive gamblers to experience more emotion regulation difficulties and more gambling behaviors. To our best knowledge, no published study has examined whether emotion regulation difficulties would mediate the relationship between intolerance of uncertainty and gambling (e.g., gambling urge and involvement in our study), whereas the mediating role of emotion regulation difficulties in the association between individuals’ negative life experience and GD has been suggested in a recent study [ 39 ]. The present study is the first to extend the model of intolerance of uncertainty to gambling and hypothesized that the two domains of difficulties in emotion regulation (impulse control difficulties and limited access to emotion regulation strategies) would bridge the association between intolerance of uncertainty and gambling urge (Hypothesis 6), as well as that between intolerance of uncertainty and gambling involvement (Hypothesis 7).…”
Section: Introductionmentioning
confidence: 74%
“…As a potential consequence of intolerance of uncertainty, emotion regulation difficulties, in turn, may increase the probability of gambling behaviors or even GD. Previous studies have consistently reported the positive correlation between emotion regulation difficulties and disordered gambling levels [ 37 , 38 , 39 ], while disordered gamblers also reported more difficulties in emotion regulation than their healthy counterparts [ 40 ]. As gambling is associated with the expectation of gaining positive emotional experience and reducing boredom and distress across age groups and cultures [ 41 , 42 , 43 ], it has long been used as a means to regulate emotional states by gamblers [ 17 , 18 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative model was estimated to test the mediating role of each variable in the relationship between GD and SCC since the dependent, and the independent variables were reversed ( Thurm et al, 2022 ). All models were estimated with maximum-likelihood parameters with standard errors and a mean-adjusted chi-square test statistic robust to non-normality (MLMV).…”
Section: Methodsmentioning
confidence: 99%